Practices towards prevention of food borne diseases among females in rural area of Trichy, India - Hemalatha, Kumarasamy; Parthiban, Elavarasan; Parthipan, Kathirvel; Parkavi, S.; Elango, S. (International Journal of Research in Medical Sciences, 2018)
Background: Food borne diseases are of great importance since it leads to multiple health problems resulting in illness, malnutrition, mortality and economic loss. These diseases share a significant proportion in the occurrence of communicable diseases. Objectives was to study the knowledge about food borne diseases and food safety among women residing in rural area. Methods: This was a cross sectional study involving 150 adult females who were residing in rural field practice areas of a tertiary care teaching hospital. Practices of safe food handling were assessed using an interviewer administered questionnaire. Informed consent was obtained, and confidentiality was maintained. Appropriate descriptive statistical analysis was done. Results: Out of 150 females, 147 (98%) were aware of the importance of washing hands before cooking. Sixty four (42.7%) females had a habit of washing the vegetables with water twice before cooking. 102(68%) females consumed stored food after reheating, 48(32%)females consumed without heating. Though 70% were aware of food adulteration, none of the participants have lodged compliant against adulteration. Conclusions: Through our study we found that most of the females practiced proper hand washing before cooking and proper storage of the leftover food. The proportion of females who followed adequate cleaning of non-vegetarian food items and vegetables were found to be inadequate.